2019
DOI: 10.3389/fphar.2019.01188
|View full text |Cite
|
Sign up to set email alerts
|

Phillyrin Attenuates Osteoclast Formation and Function and Prevents LPS-Induced Osteolysis in Mice

Abstract: As the sole cell type responsible for bone resorption, osteoclasts play a pivotal role in a variety of lytic bone diseases. Suppression of osteoclast formation and activation has been proposed as an effective protective therapy for new bone. In this study, we reported for the first time that phillyrin (Phil), an active ingredient extracted from forsythia, significantly inhibited RANKL-induced osteoclastogenesis and bone resorption in vitro and protected against lipopolysaccharide-induced osteolysis in vivo. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…As shown in Figure 2 B,C, PL significantly inhibited osteoclastogenesis in a dose-dependent manner in vitro, as evidenced by the reduced number and average area of TRAP + multinucleated (≥3 nuclei) cells. To explore at which stage of osteoclastogenesis PL exerts its suppressive effect, we incubated BMM cells with 1 µM PL at different differentiation time points, as previously described [ 25 ]. The results showed that PL treatment on day three of the five-day culture (late treatment) and treatment on the first two days of RANKL induction (early treatment) had similar and significant inhibitory effect on osteoclast formation, both of which resulted in an approximate 30% reduction in formation of TRAP + osteoclasts ( Figure 2 D,E).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2 B,C, PL significantly inhibited osteoclastogenesis in a dose-dependent manner in vitro, as evidenced by the reduced number and average area of TRAP + multinucleated (≥3 nuclei) cells. To explore at which stage of osteoclastogenesis PL exerts its suppressive effect, we incubated BMM cells with 1 µM PL at different differentiation time points, as previously described [ 25 ]. The results showed that PL treatment on day three of the five-day culture (late treatment) and treatment on the first two days of RANKL induction (early treatment) had similar and significant inhibitory effect on osteoclast formation, both of which resulted in an approximate 30% reduction in formation of TRAP + osteoclasts ( Figure 2 D,E).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are consistent with some other reports. For example, Wang et al [ 47 , 48 ] reported that phillyrin showed a protective effect against bone loss in an in vivo model by inhibiting RANKL-induced osteoclast differentiation, but did not affect osteoblast differentiation. Interestingly, phillyrin decreased RANKL expression in an in vivo model of osteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Phillyrin, an active ingredient extracted from forsythia, significantly inhibited receptor activator of nuclear factor κB ligand (RANKL)-induced osteoclastogenesis and bone resorption in vitro and protected against lipopolysaccharide-induced osteolysis in vivo. Phillyrin effectively blocked RANKL-induced activations of c-Jun N-terminal kinase and extracellular signal-regulated kinase, which suppressed the expression of c-Fos and nuclear factor of activated T-cells cytoplasmic 1 [15]. Imperatorin (IMT) reduced the release of TNF-α, IL-6 and IL-1β, inhibited the expression of iNOS and COX-2, and suppressed the activity of NF-κB via upregulation of the expression of p65 (C) and IκB (C), and downregulation of the expression of p65 (N) [16].…”
Section: Chemical Constituents Of "Sanse Powder" Prescriptionmentioning
confidence: 99%